Current Research on the decretals between Gratian's Decretum and the Liber Extra - Duggan, Anne (Ephemerides iuris canonici, 2017)
L'Autrice, una delle più autorevoli e qualificate studiose della Chiesa Medievale, presenta una sintesi dell'attuale stato delle ricerche attorno alle decretali nel periodo compreso tra la redazione del Decretum di Graziano ed il Liber Extra. The author, one of the best qualified authorities on the Medieval Church, offers a synthesis of the present state of research on the decretals in the period spanning between the composition of Gratian's Decretum and the Liber Extra.